2020
DOI: 10.1111/jonm.12944
|View full text |Cite
|
Sign up to set email alerts
|

A simple tool to evaluate the antiretroviral therapy programme in primary health care setting of Lesotho

Abstract: Aim An evaluative tool for the antiretroviral therapy programme was developed for use in the primary health care setting of Lesotho. Background Information on processes followed in the development of standardized and acceptable evaluative tools is not always available to practicing nurses. Methods Behaviours affecting the antiretroviral therapy (ART) programme were contextualized using the conceptual model for social programmes and Intervention Wheel framework. A convergent parallel mixed‐methods design was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…It is noteworthy that Nyangu and Nkosi mentioned that registered nurse midwives and nurse clinicians manage the majority of PHC facilities, and their professional titles did not affect service provision [65]. However, it was suggested that there is a need to provide more staffing to address staff shortages and reduce patients waiting times at facilities [65].…”
Section: Interventions Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that Nyangu and Nkosi mentioned that registered nurse midwives and nurse clinicians manage the majority of PHC facilities, and their professional titles did not affect service provision [65]. However, it was suggested that there is a need to provide more staffing to address staff shortages and reduce patients waiting times at facilities [65].…”
Section: Interventions Modelsmentioning
confidence: 99%
“…It is noteworthy that Nyangu and Nkosi mentioned that registered nurse midwives and nurse clinicians manage the majority of PHC facilities, and their professional titles did not affect service provision [65]. However, it was suggested that there is a need to provide more staffing to address staff shortages and reduce patients waiting times at facilities [65]. Ideally, Uys and Klopper recommended that at least one specialist nurse, five registered nurse midwives and four enrolled nurses were needed for the effective running of PHC settings [66].…”
Section: Interventions Modelsmentioning
confidence: 99%
“…Research (PIH, 2017) also revealed a high prevalence of mental disorders among PLWHA in selected regions in Lesotho. Nurses are the primary HIV treatment providers and provide most mental health services (Nyangu, 2016& Damane, 2018. However, there remains a gap in the management of mental health disorders due to a lack of training, specialist support and attention to physical illnesses in PLWHA, as is the case in most sub-Saharan African countries (Vavani et al, 2020;Ayugi, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Barriers such as lack of specialists and training, limited resources, and high patient volumes have been documented to compromise the integration of mental health in the HIV/AIDS treatment (Parcesepe, 2018;Mthinyane et al, 2021). (Ayugi, 2015;Nyangu, 2016;Ramokanate et al, 2021) identified similar challenges in the context of mental health and HIV/AIDS care in Lesotho, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Majority of health care facilities in Lesotho are managed by nurses who are qualified as either midwives or clinicians (Nyangu & Nkosi, 2019a). Lesotho is one of the few countries that permitted initiation of ART by nurses owing to the scarcity of Medical Doctors, a move that has seen a great increase of the coverage of ART (Nyangu, 2016). Such an initiative has been seen to be operative and feasible as majority of patients receive health care in the facilities located variously across the country.…”
Section: Introductionmentioning
confidence: 99%